Neonatal Esophageal Perforation with Esophageal Atresia: A Case Report - Solanki, Shailesh; Menon, Prema; Samujh, Ram (Journal of Neonatal Surgery, 2019)
Esophageal perforation (EP) in a neonate is very rare and is often iatrogenic. Preterm neonates with esophageal atresia (EA) are at more risk, as EP can occur during any test or intervention at pharyngeal region. We are presenting the management of EP in a preterm neonate with EA who presented with pneumomediastinum.